To determine whether \( g(x) \) is linear or exponential, we can analyze the values provided in the table:
\[ \begin{array}{|c|c|} \hline x & g(x) \ \hline -1 & 3 \ 0 & 2 \ 1 & 3 \ 2 & 6 \ 3 & 12 \ \hline \end{array} \]
Step 1: Check if \( g(x) \) is linear
For a function to be linear, the differences between consecutive \( g(x) \) values should be constant. Let's calculate these differences:
- \( g(0) - g(-1) = 2 - 3 = -1 \)
- \( g(1) - g(0) = 3 - 2 = 1 \)
- \( g(2) - g(1) = 6 - 3 = 3 \)
- \( g(3) - g(2) = 12 - 6 = 6 \)
The first differences are \(-1, 1, 3, 6\), which are not constant. Thus, \( g(x) \) is not linear.
Step 2: Check if \( g(x) \) is exponential
For a function to be exponential, the ratios of consecutive \( g(x) \) values should be constant. Let's calculate these ratios:
- \( \frac{g(0)}{g(-1)} = \frac{2}{3} \)
- \( \frac{g(1)}{g(0)} = \frac{3}{2} \)
- \( \frac{g(2)}{g(1)} = \frac{6}{3} = 2 \)
- \( \frac{g(3)}{g(2)} = \frac{12}{6} = 2 \)
The ratios are \(\frac{2}{3}, \frac{3}{2}, 2, 2\). The ratios are not constant, but let’s see if we can identify a consistent pattern in the values of \( g(x) \):
Step 3: Examining possible exponential growth
Looking more closely at the values could reveal an exponential pattern:
- Notice that starting from \( g(1) = 3 \), \( g(2) = 6 \) (which is \( 2 \times 3 \)) and \( g(3) = 12 \) (which is \( 2 \times 6 \)).
Step 4: Hypothesis of the form
This suggests a potential form for the function:
- It appears that:
- From \( g(1) \) to \( g(2) \), we multiply by 2.
- From \( g(2) \) to \( g(3) \), we also multiply by 2.
To model this, we can set \( g(x) = a \cdot b^x \).
Step 5: Finding parameters \( a \) and \( b \)
From the table values:
- Let’s take the point \( g(1) = 3 \):
\[ 3 = a \cdot b^1 \rightarrow a \cdot b = 3 \quad (1) \]
- Now, for \( g(2) = 6 \):
\[ 6 = a \cdot b^2 \quad (2) \]
Dividing (2) by (1): \[ \frac{6}{3} = \frac{a \cdot b^2}{a \cdot b} \quad \Rightarrow 2 = b \]
Putting \( b = 2 \) back into (1): \[ a \cdot 2 = 3 \quad \Rightarrow a = \frac{3}{2} \]
Conclusion: Write the equation
Thus, the function \( g(x) \) can be expressed as:
\[ g(x) = \frac{3}{2} \cdot 2^x \]
This confirms that \( g(x) \) is an exponential function. Therefore, the final answer is:
\[ g(x) = \frac{3}{2} \cdot 2^x \]